SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN HOTEL DI TANGERANG MENGGUNAKAN METODE AHP DAN TOPSIS - Herry Sukma; Fenina Twince Tobing; Rena Nainggolan (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Banten Province has a city, namely Tangerang, to be precise in the northern part of Banten City. There are many tourist attractions that we can visit in the city of Tangerang, such as natural scenery, historical places, natural scenery, photo spots and culinary tours. With various tourist attractions in the city of Tangerang, it attracts tourists who want to travel to these places. With so many interested tourists visiting the city of Tangerang, the existing hotel is one of the destinations for tourists who are visited for a place to stay and rest. This has had an impact on the increasing number of hotels in the area, which has led to an increasing variety of choices for tourists. To make it easier for tourists to choose a hotel according to their needs, a decision support system is needed in choosing a hotel to use for a place to stay and rest. Tourists can choose hotels according to their desired needs by using a decision support system with various criteria. The decision support system applies the initial criteria weighting by using the AHP method and hotel alternative ranking using the TOPSIS method. The system has been tested and implemented by distributing questionnaires to 30 respondents using the USE Questionnaire and applying the Sala Likert Method to perform the questionnaire calculations, and the final result obtained in the calculation of the questionnaire is 84.51%.